Positive outcomes of oil palm phenolics on degenerative diseases in animal models - Sambanthamurthi, Ravigadevi; Tan, Yew Ai; Sundram, Kalyana; Hayes, Kenneth C.; Abeywardena, Mahinda; Leow, Soon Sen; Sekaran, Shamala Devi; Sambandan, T.G.; Rha, Cho Kyun; Sinskey, Anthony J.; Subramaniam, Krishnan; Fairus, Syed; et al. (Cambridge University Press, 2011)
It is well established that plant phenolics elicit various biological activities, with positive effects on health. Palm oil production results in large volumes of aqueous by-products containing phenolics. In the present study, we describe the effects of oil palm phenolics (OPP) on several degenerative conditions using various animal models. OPP reduced blood pressure in a NO-deficient rat model, protected against ischaemia-induced cardiac arrhythmia in rats and reduced plaque formation in rabbits fed an atherogenic diet. In Nile rats, a spontaneous model of the metabolic syndrome and type 2 diabetes, OPP protected against multiple aspects of the syndrome and diabetes progression. In tumour-inoculated mice, OPP protected against cancer progression. Microarray studies on the tumours showed differential transcriptome profiles that suggest anti-tumour molecular mechanisms involved in OPP action. Thus, initial studies suggest that OPP may have potential against several chronic disease outcomes in mammals.